The Influence of Drilling-Fluid Rheology on Cuttings-Bed Behavior - Werner, Benjamin (2018)
Transporting cuttings out of the wellbore is an important part of every drilling operation to ensure efficiency and the reduction of non-productive time. The drilling fluids used for this task are complex fluid systems, generally with either oil or water as a base substance. The hole-cleaning performance of these two fluid systems is reportedly different from each other. Industry experience has shown that oil-based drilling fluids are performing better than water-based drilling fluids, even when the viscosity is similar. Additionally, research results reported in the literature show diverse conclusions with superior behavior for either water-based or oil-based fluids, or findings where neither of the types excelled. A general conclusion has not been made and the reasons for the different behavior are not entirely understood. The present thesis investigates the influence of the viscoelastic properties of drilling fluids on cuttings transport and hole cleaning. For this purpose an extensive rheometer study was conducted to measure the rheological properties of drilling fluids. Flow-loop experiments compare the performance of these fluids regarding their hole cleaning and cuttings-transport abilities in a controlled experimental setup. The tested fluids were three oil based and one water-based drilling fluid. The oil-based fluids were water-in-oil emulsions with a yield stress (named OBM A, B, and C), containing barite, CaCl2, bentonite, lime, emulsifier, and a fluid loss agent. The water-based fluid was a KCl fluid, viscosified with xanthan gum. Other additives were glycol, polyanionic cellulose, starch, soda ash and barite. OBM B and the KCl fluid were adjusted to have a similar viscosity profile in the relevant shear-rate range of the flow-loop experiments. The fluid composition and description is presented in chapter 2.2. The rheological investigation involved a preconditioning study, measurement of high shear rate and low shear-rate flow curves, measurement of temperature dependence, amplitude-sweep tests, ...